Determination of Acetaminophen in Jamu Pegal Linu by High Performance Liquid Chromatography - Mamat Pratama; Dian Harisman; Lukman Labasy; Seniwati Seniwati; Muammar Fawwaz (Universitas Muslim Indonesia, 2022)
Traditional medicine is very popular in Indonesia, so it is necessary to do this research to analyze the presence or absence of chemical substances contained in traditional medicine. This research aims to determine acetaminophen content on jamu pegal linu circulating in Makassar city by High Performance Liquid Chromatography (HPLC). The jamu were obtained from several drugs stores near Terong traditional market. Five brands of jamu pegal linu detected their acetaminophen content by HPLC method using a UV-Visible SPD 20A detector with a wavelength of 254 nm. The result showed that chromatogram on jamu pegal linu is the same as the acetaminophen at the retention time of 5.28 minutes. The whole of jamu pegal linu analyzed positively contain acetaminophen and prohibited for consumption in accordance with the regulations of National Agency of Drug and Food Control (POM) Republic Indonesia No.KH.00.01.43.2773/2008.